2008
DOI: 10.1016/j.jss.2007.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Lymph Node Metastases and Ratio in Esophageal Cancer

Abstract: Background-The incidence of carcinoma of the distal esophagus and GE junction is rapidly increasing. A large single-center experience was reviewed to determine the impact of lymph node positivity and ratio on survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 13 publications
2
55
0
Order By: Relevance
“…These modifications reflect findings which show improved prognostic stratification with consideration of the number ofdiseased lymph nodes [13,[84][85][86]. Several studies have shown the number of positive lymph nodes to be an independent prognostic indicator [13,14,[87][88][89][90].…”
Section: Number Of Positive Lymph Nodesmentioning
confidence: 56%
“…These modifications reflect findings which show improved prognostic stratification with consideration of the number ofdiseased lymph nodes [13,[84][85][86]. Several studies have shown the number of positive lymph nodes to be an independent prognostic indicator [13,14,[87][88][89][90].…”
Section: Number Of Positive Lymph Nodesmentioning
confidence: 56%
“…More than 65% of patients with localized esophageal cancers and negative resection margin have a positive lymph node at the time of surgery [1]. However, despite complete tumor resection and extensive lymphadenectomy, systemic and local recurrence is common [2] and the five-year survival rate is 15-39% [3].…”
Section: Introductionmentioning
confidence: 99%
“…More than 65% of patients with localized esophageal cancers and negative resection margin have a positive lymph node at the time of surgery [1]. However, despite complete tumor resection and extensive lymphadenectomy, systemic and local recurrence is common [2] and the five-year survival rate is 15-39% [3].The discovery over the last decade of markers of lymphatic endothelial cells like podoplanin (D2-40) [4], LYVE-1 [5] and Prox 1 [6], and the development of novel antibodies to these markers, have generated …”
mentioning
confidence: 99%
“…In many human cancers, metastasis to the regional lymph node is one of the most significant predictors of patient outcome (8,9). Lymph node metastasis is associated with decreased papillary thyroid carcinoma survival and increased risk of local recurrence.…”
Section: ) In Addition High Sphingosine Kinase 1 Expression Was mentioning
confidence: 99%